CAPITAL STRUCTURE EFFECT ON FINANCIAL PERFORMANCE OF TELECOMMUNICATION COMPANIES LISTED IN INDONESIA STOCK EXCHANGE. - Petra, Wangania Micha Lingkan; Lapian, S.L.H.V. Joyce; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2017)
Despite the abundance opportunity, most of Indonesian telecommunication companies shows weak financial performance. One of the strategies to boost the financial performance is by manage the level of debt used as capital. This research is conducted with the aim to see how far is the impact of capital structure towards financial performance in Indonesian telecommunication industry. The capital structure is measured by debt to asset ratio (DAR) and debt to equity ratio (ER). Performance is measured return on asset (ROA). All telecommunication companies that listed in Indonesia Stock Exchange are included in the population of this research. To determine the sample, purposive sampling method is used and telecommunication companies that meet the criteria has chosen and provide 39 data after removing 1 data outliers. This research used multiple regression analysis to test the hypotheses. This model of regression is able to explain ROA by 61% stated by the R2 value, and as for the results, DAR proven to have negative and significant effect towards return on asset. While DER shows negative but insignificant effect on return on asset. Â Keywords: capital structure, debt financing, dar, der, roa, financial performance.Â